MODEL ECONOMIC ORDER QUANTITY (EOQ) DAN MODEL OPTIMISASI ROBUST DALAM PENENTUAN PERSEDIAAN ALAT SUNTIK (SPUIT) - SAGITA, PUTRI BELLA; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (E-Jurnal Matematika; Vol 8 No 3 (2019)DO - 10.24843/MTK.2019.v08.i03.p248, 2019)
The purpose of this research is to determine and analyze the minimum order quantities and the supply cost through Economic Order Quantity (EOQ) Model without Stock Out, EOQ Model with Buffer Stock, and Robust Optimization. EOQ model without Stock Out is an inventory model with a fixed number of requests and a fixed period of demand so the goods are considered always available or there is no stock out. Whereas EOQ Model with Buffer Stock is an inventory model with uncertainty demand during the lead time that described with a uniform density function. Another model is Robust Optimization Model that is used for cases with uncertainty demand. The results showed that the minimum order quantities through EOQ Model without Stock Out and EOQ Model with Buffer Stock was almost the same value but the cost was more minimum with the EOQ Model with Buffer Stock. Whereas, through the Robust Optimization Model there are different minimum order quantities for each period with a minimum supply cost compared to the two previous models. This occurs in both types of Spuit, namely Spuit Terumo 3 mL and Spuit Terumo 5 mL.